Use of communicative activities and English Language Learning in basic level students at the language center of Cesar Vallejo University. - Sánchez Martínez, Diana Elizabeth (2018)
The thesis entitled Use of communicative activities and English language learning in basic level students at the language center of Cesar Vallejo university, had as general hypothesis that the use of communicative activities is significantly related to English language learning in basic level students at the language center of Cesar Vallejo University, Comas, 2017. This research has been of fundamental/descriptive type and quantitative approach with a correlational design. The population and sample were 23 students who studied Basic English at the language center of Cesar Vallejo University. After processing the results and performing the appropriate and necessary testing, the initial hypothesis was finally found to be true, confirming that the use of communicative activities is significantly related to English language learning in basic level students at the language center of Cesar Vallejo University, Comas, 2017.